Can method data dependencies support the assessment of traceability between requirements and source code?. Issue 11 (9th September 2015) - Kuang, Hongyu; Mäder, Patrick; Hu, Hao; Ghabi, Achraf; Huang, LiGuo; Lü, Jian; Egyed, Alexander
Abstract: Requirements traceability benefits many software engineering activities, such as change impact analysis and risk assessment. However, these activities require complete and correct traceability links which is not trivial, making traceability assessment an important field of study. In recent years, requirements traceability research has focused on using call dependencies within source code to understand how code properties contribute to the implementation of a requirement and to assess whether traceability links are correct and complete. These approaches largely ignore the role of existing data dependencies within the source code. That is, methods may never call each other, but may still depend upon another by sharing data. We identified five research questions and validated them on five software systems, covering 4 to 72 KLOC. We found that data dependencies are as relevant as call dependencies for assessing requirements traceability. Even more interesting, our analyses show that data dependencies complement call dependencies in the assessment. These findings have strong implications on code understanding, including trace capture, maintenance, and validation techniques. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Requirements traceability needs to be complete and correct to benefit software engineering activities, which is not trivial and making traceability assessment very important. In this paper, we find that method call and data dependencies combined resulted in significant improvements in both precision and recall compared with considering call dependencies only for traceability assessment. Meanwhile, our findings are robust against trace incompleteness and incorrectness, which implies that our findings can benefit real‐world traceability scenarios where techniques have to process imperfect traceability.